Bacterial isolates and antimicrobial susceptibility in children with acute diarrhea at Ibn Sina Medical College, Bangladesh - Akter, Sonia; Ferdousi, Reena Saad; Siddiqua, Mahmuda (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Backround: Infectious diarrhea is one of common cause of children diarrhea causing mortality and morbidity worldwide. This study was performed to identify the common bacteria and their antimicrobial susceptibility in children with diarrhea. Methods: A retrospective study was conducted from April 2014 to March 2016 at IBN SINA Medical College Hospital, Bangladesh. Stool samples were cultured on MacConkey agar and blood agar. A standard biochemical procedure was used for full identification of bacterial isolates. Antimicrobial susceptibility tests were done on Mueller-Hinton agar by using disc diffusion method. Data were entered and analyzed by using SPSS version 20 and a p-value of < 0.05 was considered statistically significant. Results: A total of 186 stool samples were tested for bacterial isolation and 55 (29.57%) cases were found to have bacterial isolates. From the total bacterial isolates, the predominant isolate was E. coli 39 (70.91%) followed by Salmonella 9 (16.36%) and Shigella Spp.7 (12.73%). As much as 84.62% E. coli were resistant to co-trimoxazole and cefuroxime while 92.31% E. coli were sensitive to amikacin and 71.79% were sensitive to cefepime and gentamicin. Salmonella were 100% sensitive to cefepime, ceftriaxone, cefixime, ceftazidime, and ciprofloxacin. Shigella were 85.71% sensitive to amikacin and cefepime. Conclusion: The results show that E. coli were the most frequently isolated pathogen in children. The majority of the bacterial isolates were resistant to multiple antibiotics. Hence, antibiotics susceptibility test is mandatory before prescribing any antibiotics.